CRISPR/Cas9‐mediated homology donor repair base editing confers glyphosate resistance to rice (Oryza sativa L.) - Sony, Sonia Khan; Kaul, Tanushri; Motelb, Khaled Fathy Abdel; Thangaraj, Arulprakash; Bharti, Jyotsna; Kaul, Rashmi; Verma, Rachana; Nehra, Mamta (Frontiers in Plant Science, 2023)
Globally, CRISPR-Cas9–based genome editing has ushered in a novel era of crop advancements. Weeds pose serious a threat to rice crop productivity. Among the numerous herbicides, glyphosate [N-(phosphonomethyl)-glycine] has been employed as a post-emergent, broad-spectrum herbicide that represses the shikimate pathway via inhibition of EPSPS (5′-enolpyruvylshikimate-3-phosphate synthase) enzyme in chloroplasts. Here, we describe the development of glyphosate-resistant rice lines by site-specific amino acid substitutions (G172A, T173I, and P177S: GATIPS-mOsEPSPS) and modification of phosphoenolpyruvate-binding site in the native OsEPSPS gene employing fragment knockout and knock-in of homology donor repair (HDR) template harboring desired mutations through CRISPR-Cas9–based genome editing. The indigenously designed two-sgRNA OsEPSPS-NICTK-1_pCRISPR-Cas9 construct harboring rice codon-optimized SpCas9 along with OsEPSPS-HDR template was transformed into rice. Stable homozygous T2 edited rice lines revealed significantly high degree of glyphosate-resistance both in vitro (4 mM/L) and field conditions (6 ml/L; Roundup Ready) in contrast to wild type (WT). Edited T2 rice lines (ER1–6) with enhanced glyphosate resistance revealed lower levels of endogenous shikimate (14.5-fold) in contrast to treated WT but quite similar to WT. ER1–6 lines exhibited increased aromatic amino acid contents (Phe, two-fold; Trp, 2.5-fold; and Tyr, two-fold) than WT. Interestingly, glyphosate-resistant Cas9-free EL1–6 rice lines displayed a significant increment in grain yield (20%–22%) in comparison to WT. Together, results highlighted that the efficacy of GATIPS mutations in OsEPSPS has tremendously contributed in glyphosate resistance (foliar spray of 6 ml/L), enhanced aromatic amino acids, and improved grain yields in rice. These results ensure a novel strategy for weed management without yield penalties, with a higher probability of commercial release.